Eco-friendly synthesis of silver nanoparticles: Enhancing optimization reaction, characterization, and antimicrobial properties with Lantana camara from geothermal area - Pati Kemala; Rinaldi Idroes; Khairan Khairan; Muliadi Ramli; Binawati Ginting; Zuchra Helwani; Rifki Aulia; Ghazi Mauer Idroes; Muhammad Yusuf; Rustam Efendi (South African Journal of Chemical Engineering)
Green synthesis methods for producing silver nanoparticles (AgNPs) have garnered significant attention for their potential in medical applications. Despite the known potential of Lantana camara in AgNP synthesis, there is a lack of studies investigating its application when grown in extreme geothermal environments, which may influence the properties and efficacy of the synthesized nanoparticles. This research aimed to fabricate AgNPs utilizing aqueous extract from L. camara, a plant growing in an extreme geothermal manifestation area. Another aim of this study is to evaluate their antimicrobial activity. Qualitative and quantitative phytochemical analyses of the plant's leaves were also conducted. Reaction optimization was performed using response surface methodology (RSM), employing a central composite design (CCD) approach. The characterization of AgNPs involved UV–vis spectroscopy, FTIR, SEM-EDX, and PSA. The antimicrobial testing was conducted against Gram-positive bacterium (S. aureus), Gram-negative bacterium (E. coli), and the fungus (C. albicans). The phytochemicals analysis revealed that the L. camara leaf extract contains flavonoids, phenolics, saponins, tannins, and steroids, lacking alkaloids and terpenoids, with total phenolic and flavonoid contents of 11.94 mg (GAE/g) and 6.70 mg (QE/g), respectively. The AgNPs exhibited a spherical shape with a surface plasmon resonance (SPR) peak at a wavelength of 417 nm, and the smallest particle size measured was 44 nm. Based on FTIR analysis, AgNPs have functional groups such as OH, NH, CC, and CH that were identified as groups involved in the reduction of Ag+ to Ag0 during the green synthesis of AgNPs. The AgNPs demonstrated the lowest antifungal activity against C. albicans. In summary, the aqueous leaf extract of L. camara from geothermal manifestation areas can serve as a bioreductant for AgNPs, exhibiting higher antibacterial activity against Gram-positive bacteria compared to Gram-negative ones.